From windfall sharing to property ownership: Prosocial personality traits in giving and taking dictator games - Kun Zhao; Yoshihisa Kashima; Luke D. Smillie (Games, 2018)
The dictator game is a well-known task measuring prosocial preferences, in which one person divides a fixed amount of windfall money with a recipient. A key factor in real-world transfers of wealth is the concept of property ownership and consequently the related acts of giving and taking. Using a variation of the traditional dictator game (N = 256), we examined whether individual differences under different game frames corresponded with prosocial personality traits from the Big Five (politeness, compassion) and HEXACO (Honesty-Humility, Emotionality, eXtraversion, Agreeableness, Conscientiousness, Openness to Experience) (honesty-humility, agreeableness) models. In the Big Five model, the effects of prosocial personality traits were generally stronger and more consistent for taking than for giving, in line with a 'do-no-harm' explanation, whereby prosocial individuals felt less entitled to and less willing to infringe on the endowments of others. In contrast, HEXACO honesty-humility predicted allocations across both frames, consistent with its broad association with fair-mindedness, and providing further evidence of its role in allocations of wealth more generally. These findings highlight the utility of integrating personality psychology with behavioral economics, in which the discriminant validity across prosocial traits can shed light on the distinct motivations underpinning social decisions.
Keywords: 330; dictator game; framing effects; personality; Big Five; agreeableness; honesty-humility